2007
DOI: 10.1021/bi7015553
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Membrane Pore Formation by Multimeric/Oligomeric Antimicrobial Peptides

Abstract: The pore-forming antibacterial peptide magainin 2 was made divalent, tetravalent, and octavalent via a copper(I)-mediated 1-3 dipolar cycloaddition reaction ("click" chemistry). This series of pore-forming compounds was tested in vitro for their ability to form pores in large unilamillar vesicles (LUVs). A large increase in the pore-forming capability was especially observed with the tetravalent and octavalent magainin compounds in the LUVs consisting of DOPC, and the octavalent magainin compound showed a mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 22 publications
2
65
0
Order By: Relevance
“…20 As depicted in Figure 1, an Ag|AgCl electrode was inserted into each droplet to enable bilayer capacitance measurements and electrical bilayer recordings with single ion channel sensitivity. Bilayers were made from 1,2-dioleoyl-sn-3-phosphatidylcholine (DOPC), a synthetic lipid extensively used for membrane permeabilization studies of membrane-degrading compounds such as bacterial toxins and antimicrobial peptides, 21 or from asolectin, a natural lipid extract that, like mammalian plasma membranes, includes sterols that render the membrane more rigid. 22 For both lipid compositions, a stable current of typically 5 pA with a peak-to-peak noise of ∼6 pA was measured at an applied dc voltage of þ100 mV (Figure 2a,d,g).…”
Section: Resultsmentioning
confidence: 99%
“…20 As depicted in Figure 1, an Ag|AgCl electrode was inserted into each droplet to enable bilayer capacitance measurements and electrical bilayer recordings with single ion channel sensitivity. Bilayers were made from 1,2-dioleoyl-sn-3-phosphatidylcholine (DOPC), a synthetic lipid extensively used for membrane permeabilization studies of membrane-degrading compounds such as bacterial toxins and antimicrobial peptides, 21 or from asolectin, a natural lipid extract that, like mammalian plasma membranes, includes sterols that render the membrane more rigid. 22 For both lipid compositions, a stable current of typically 5 pA with a peak-to-peak noise of ∼6 pA was measured at an applied dc voltage of þ100 mV (Figure 2a,d,g).…”
Section: Resultsmentioning
confidence: 99%
“…To consider the role of lipid II as molecular target and its impact on binding intensity, 0.1 mol% lipid II was added to the matrix lipids. In accordance to other peptide/model membrane studies [27][28][29][30][31][32][33] and to avoid non-specific binding of the cationic antimicrobial peptides to the membrane surface, DOPC was initially selected as membrane lipid. As depicted in Fig 2A, [34,35], the gallidermin structure ( Fig.…”
Section: Kinetics Of Peptide Binding To Model Membranesmentioning
confidence: 99%
“…The modes of action have been reviewed in detail (3,25,27,39,41), and new modes of action are still emerging (14). Peptides are being found that modulate the immune response or have targets within the cell (19), many peptides bind and permeate cell membranes (1,29), and others have multiple targets (16). Taking these findings together, AMPs display robust mechanisms that could decrease the possibility for resistance to develop (18,28).…”
mentioning
confidence: 99%